ChemInform Abstract: A New Photoclick Reaction Strategy: Photo‐Induced Catalysis of the Thiol‐Michael Addition via a Caged Primary Amine. Issue 37 (22nd August 2013) - Xi, Weixian; Krieger, Matthias; Kloxin, Christopher J.; Bowman, Christopher N.
Abstract The utilization of 2‐(2‐nitrophenyl)propyloxycarbonyl as a photolabile primary amine cage enables the thiol‐Michael ′click′ reaction to be photo‐triggered.